Sustainability in the hospitality industry principles of sustainable operations - Legrand, Willy; Chen, Joseph S.; Laeis, Gabriel C. M. (Routledge, Taylor & Francis Group, 2023)
"This foundational textbook investigates the economic, environmental, and social sustainability issues facing the hospitality industry today, and explores ideas, solutions, strategies of how to manage operations in a sustainable way. This updated fourth edition features new content including: Research on nature-based solutions and zero carbon approaches in facilities; technologies for energy; water and waste management; changes in consumer behaviour; and environmental and social impacts of food production A new chapter on employees, diversity, inclusion and well-being in the industry A new chapter on the challenges of operating in the Global South More than 100 international industry case studies and focused info boxes New practical exercises, discussion questions, and research project ideas based on real-life sustainability scenarios Accessible and comprehensive, this book is essential reading for all students as well as current and future managers in the hospitality industry"--